Prevalence of Hypocalcemia and Raised Serum Alkaline Phosphatase Levels Among Children Taking Antiepileptic Drugs - Mehboob, Hafiz Aaqib; Ashraf, Sohail; Khan, Haisam; Safdar, Shiza (Indus Journal of Bioscience Research, 2025)
Background: Epilepsy in children is treated by antiepileptic drugs, which cause imbalances of mineral metabolism such as hypocalcemia and acquired elevated alkaline phosphatase levels. These biochemical markers need careful monitoring to interpret the long-term outcomes of the treatment of AED. Objective: To determine the frequency of hypocalcemia and raised serum alkaline phosphatase among children with epilepsy taking anti-epileptic drugs in a tertiary care hospital. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from November 2023 to May 2024 at the Department of Pediatrics, POF Hospital, Wah Cantt. Methodology: A total of 91 children aged 3 to15 years, diagnosed with epilepsy and receiving AEDs for at least six months, were included in the study. Serum calcium and ALP levels were measured, and their prevalence was assessed. Results: The mean age of the patients was 8.76 ± 3.30 years, with 67% of children shown hypocalcemia and 69.2% showing elevated ALP levels. The prevalence of hypocalcemia was highest in children on phenobarbital (84%), followed by valproic acid (71.4%) and carbamazepine (48.4%). Conclusion: Our study found a strong link between chronic antiepileptic drug (AED) use and bone metabolism disturbances, such as elevated alkaline phosphatase and hypocalcemia. Classical AEDs like valproic acid and phenobarbital significantly affect bone health. Regular monitoring of children on long-term AEDs is recommended, with possible vitamin D and calcium supplementation. Further research with larger, multi-centered populations is needed to validate these findings and guide appropriate interventions.